Modifying Effect of Amphipatic Compounds on Erythrocyte Sensitivity to the Change in the Medium Osmotic and Temperature Conditions - Abualasal, F.; Melikhova, S. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of amphipatic compounds on the erythrocyte sensitivity to hypertonic stress when transferring into 4.0 M NaCl and hypertonic cryohemolysis under cooling from 37 down to 0Â°C was investigated. It was established, that independently on the nature of the acting agent its effect on cell preservation under hypertonic hemolysis and hypertonic stress was the similar. The concentration range, where the protective effect is maximum, is manifested under hypertonic stress for each studied compound. Under high amphipate concentrations under hypertonic conditions the prohemolytic effect of the compound is noted. When transferring into 4.0 M NaCl the protective effect of amphipate is also manifested in a change of temperature dependence of erythrocyte susceptibility to hypertonic stress.